Laparoscopic colorectal surgery and discharge within 24 h—who is at risk for readmission?. (18th July 2021) - de Azevedo, José Gonçalves Moreira; Mendes, Carlos Ramon Silveira; Lima, Meyline Andrade; Pessoa, Joana Carolina Saraiva de Paula; São Julião, Guilherme Pagin; Perez, Rodrigo Oliva; Vailati, Bruna Borba
Abstract: Aim: The aim was to describe risk factors for hospital readmission in patients undergoing laparoscopic colorectal procedures and being discharged in ≤24 h. Method: All consecutive patients undergoing minimally invasive colorectal surgery between 2010 and 2019 from a single institution were retrospectively reviewed. All patients were included in an enhanced recovery programme. Patients who met criteria for hospital discharge were compared according to the need for readmission in a 45‐day follow‐up. Results: In all, 664 patients underwent minimally invasive colorectal surgery during the study period and 237 (35.7%) were discharged in ≤24 h. Readmission was required in 16 (6.8%) patients discharged in ≤24 h and no postoperative mortality was observed in this group. Patients discharged in ≤24 h were more likely to have benign disease ( P < 0.001), fewer associated procedures ( P < 0.025) and intracorporeal anastomoses ( P < 0.001). The type of surgical procedure (abdominoperineal resection), low rectal tumour, malignant disease, older age and longer operating time were associated with readmission. Age (OR 1.06; P = 0.037), malignant disease (OR 4.39; P = 0.05) and operating time (OR 1.03; P < 0.001) were identified as independent predictive factors for readmission amongst patients being discharged in ≤24 h. Conclusion: Highly selected patients undergoing minimally invasive procedures in colorectal surgery may be safely discharged within 24 h following the procedure. High‐risk features for readmission include older age, malignant disease and longer operating time.